Keanekaragaman Jenis Kupu-Kupu Famili Nymphalidae di Kawasan Bukit Cogong - Merti Triyanti; Destien Atmy Arisandy (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2019)
This study aims to determine the diversity index of the species of nympalidae family in the Cusi Hill area of ​​Musi Rawas. This research uses exploration and description methods using transect roaming techniques. The observation station was determined to be 3 stations with 5 transects systematically with a transect area of ​​100m x 100m. Catching using net net, identification by observing the morphological characteristics of the nympalidae family butterfly. Based on the study, 106 data obtained from dragonflies from 12 species of butterflies from 6 families of nympalidae, namely Junonia athletes, Ideopsis juventa, Junoni orithya, Cupha erymanthis, Micalesis mineus, Junonia almana, Melanitis leda, Danaus genutia, Ideopsis juventa, Junoni orithya, Cupha erymanthis, Micalesis mineus, Junonia almana, Melanitis leda, Danaus genutia, Euploea mulciber, Euploea eunhaa, Phupa columella, and Doleschallia bisaltide. The lowest species composition was Phaedyma columella, and Doleschallia bisaltide by 1.89%, while the highest was Junonia athletes by. 33.01%. Conclusion The diversity index of the butterfly species of nympalidae family in Bukit Cogong, Musi Rawas Regency is in the medium category with a value of 2.48. uniformity index at all stations in the high category, stable community and dominance index (C) in all stations in the low category. Keywords: diversity, butterflies, family nympalidae, bukit cogong